FINANCIAL ASPECTS OF SUPPORT THE BUSINESS-SECTOR OF UKRAINE ARE IN THE CONDITIONS OF THE MILITARY STATE - Sakun , O.S.; Shchur , R.I.; Matskiv , V.V. (The actual problems of regional economy development, 2022)
The article is devoted the analysis of the modern state of business and separate aspects him sponsorship in Ukraine in the Russian-Ukrainian war-time. Under circumstances plenty of destructions of civil objects and objects of infrastructure on all territory of our country, forced migration of population, through military aggression, inflationary processes, dissolution of the commercial acceding to Republic Byelorussia and blocking of Ukrainian ports domestic business found oneself on verge of existence. Taking into account importance of stabilizing of national economy for the sake of possibility of the subsequent financing the country of the military ability, liquidation of consequences and support of a victim, from Russian-Ukrainian war, extraordinary actuality is acquired by the question of sponsorship of enterprises and businessmen of Ukraine in the conditions of the military state, as exactly a business-sector is the basic source of the tax entering budget. The purpose of the article is opening and systematization of key financial aspects of support of domestic business in the conditions of the military consisting of Ukraine. Gaining end is provided the use of such methods, as an analysis and synthesis, generalization and scientific abstraction. By the state on today the Ukrainian economy functions only half. Working part is mainly made by the enterprises of critical infrastructure, which give services a population in the field of medicine, water-supply, energy supply, gas-supplying, production and realization of food stuffs, and by other groups of commodities of everyday consumption. However possible work even of these enterprises is only on controlled by Ukraine territories and those territories, where military operations are not. At support of international partners and on the basis of reformation of tax legislation the substantial steps of sponsorship of domestic enterprises and businessmen are already done in Ukraine, however much these initiatives need deepening and expansion with the purpose of subsequent renewal of national economy, which must be arrived at by renewal and development of such spheres as agrarian business, food industry, pharmaceutics, light industry, trade and providing resources. Development and strengthening of own economic feasibilities, complete liquidation of any economic connections, with countries-aggressors, development of the European collaboration due to the output of domestic producers on a new level will help not only to accelerate victories and complete war but also will lay the foundation of the economy growing and rapid renewal of our country.